Exosomes From Adipose-Derived Stem Cells: The Emerging Roles and Applications in Tissue Regeneration of Plastic and Cosmetic Surgery - Xiong, Mingchen; Zhang, Qi; Hu, Weijie; Zhao, Chongru; Lv, Wenchang; Yi, Yi; Wu, Yiping; Wu, Min (Frontiers in Cell and Developmental Biology, 2020)
Adipose-derived stem cells (ASCs) are an important stem cell type separated from adipose tissue, with the properties of multilineage differentiation, easy availability, high proliferation potential, and self-renewal. Exosomes are novel frontiers of intercellular communication regulating the biological behaviors of cells, such as angiogenesis, immune modulation, proliferation, and migration. ASC-derived exosomes (ASC-exos) are important components released by ASCs paracrine, possessing multiple biological activities. Tissue regeneration requires coordinated “vital networks” of multiple growth factors, proteases, progenitors, and immune cells producing inflammatory cytokines. Recently, as cell-to-cell messengers, ASC-exos have received much attention for the fact that they are important paracrine mediators contributing to their suitability for tissue regeneration. ASC-exos, with distinct properties by encapsulating various types of bioactive cargoes, are endowed with great application potential in tissue regeneration, mechanically via the migration and proliferation of repair cells, facilitation of the neovascularization, and other specific functions in different tissues. Here, this article elucidated the research progress of ASC-exos about tissue regeneration in plastic and cosmetic surgery, including skin anti-aging therapy, dermatitis improvement, wound healing, scar removal, flap transplantation, bone tissue repair and regeneration, obesity prevention, fat grafting, breast cancer, and breast reconstruction. Deciphering the biological properties of ASC-exos will provide further insights for exploring novel therapeutic strategies of tissue regeneration in plastic and cosmetic surgery.